Penambahan Etanol sebagai Ekstraktor Lignin dalam Mengurangi Konsumsi NaOH Dan Degradasi Fiber Pada MCO₂ Stage - Gilang Garnadi Suryadi; Yella Veliana Kesuma; Nurul Ajeng Susilo; Rizal Pauzan Ramdhani (Department of Chemical Engineering, Politeknik Negeri Bandung, 2024)
One of the stages in the pulp industry that needs a lot of NaOH is MCO₂ (Medium Consistency Oxygen). However, the production process is impeded by the highly restricted availability of NaOH. Additionally, the significant fiber degradation that frequently takes place at the MCO2 stage may lessen the pulp's viscosity and strength. The study's components included pulp, ethanol, and NaOH. The goal of the research was to use less NaOH and to slow down fiber degradation by adding ethanol. The process involves adjusting the dose to obtain the optimum proportion of ethanol and NaOH, after which the temperature and reaction time are varied to produce pulp with higher quality. The results showed that at various doses, 50%:50% was the most optimum proportion of ethanol and NaOH with a kappa number 18, viscosity 1068.11 cP, and brightness 32.15%ISO. The best temperature that occurred in the optimum proportion of ethanol and NaOH was 85°C with a kappa number of 17.3, a viscosity of 1056.78 cP, and a brightness of 32.56%ISO. Meanwhile, the best reaction time for the optimum proportion of ethanol and NaOH occurred at 90 minutes with a kappa number of 15.6 viscosity of 1023,04 cP, and brightness 32.69%ISO